2009
DOI: 10.4049/jimmunol.0901780
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Mediated and Lectin-Like Activities of Carp (Cyprinus carpio) TNF-α

Abstract: Functional characterization of TNF-α in species other than mammalian vertebrates is limited, and TNF-α has been studied in a limited number of fish species, primarily in vitro using recombinant proteins. Studies on TNF-α from different fish species so far pointed to several inconsistencies, in particular with respect to some receptor-mediated activities of fish TNF-α, such as the ability to directly activate phagocytes. In the present study a comprehensive analysis of in vitro as well as in vivo biological act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 87 publications
1
39
1
2
Order By: Relevance
“…In contrast to the notion that fish TNF-a cannot directly activate phagocytes (macrophages) (37,38), the trout macrophagelike RTS-11 cell line responded to rTNF-a3 stimulation. We confirmed our results by stimulating primary macrophages with rTNF-a3.…”
Section: Bioactivity Of Rtnf-a3mentioning
confidence: 63%
See 2 more Smart Citations
“…In contrast to the notion that fish TNF-a cannot directly activate phagocytes (macrophages) (37,38), the trout macrophagelike RTS-11 cell line responded to rTNF-a3 stimulation. We confirmed our results by stimulating primary macrophages with rTNF-a3.…”
Section: Bioactivity Of Rtnf-a3mentioning
confidence: 63%
“…Roca et al (37) reported that sea bream TNF-a cannot upregulate the expression of IL-6 or TNF-a and has only minor effects on the expression of IL-1b, IL-8, and COX-2 that could have resulted from contamination with other cells in the primary macrophage cultures. The carp rTNF-a molecules also were not able to induce proinflammatory cytokine expression in macrophages/phagocytes (38). Indeed, it was suggested that fish TNF-a has no direct effect on macrophages and that the main proinflammatory effects are mediated through the activation of endothelial cells (37,38).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the last few years, recombinant TNF-␣ proteins from several fish species have been produced, and their effects on immune cells and tissues have been investigated (23,24,26,28,36,38,39,45,47,49). However, there is no information available to date on the metabolic effects of homologous recombinant TNF-␣ in nonimmune cells or tissues from fish.…”
mentioning
confidence: 99%
“…Although related, T. borreli and T. carassii induce fundamentally different immune responses in the carp host (reviewed in . For example, in T. borreli-infected carp, gene expression profiles show up-regulated expression of cytokines including ifnγ (Stolte et al, 2008) and tnfα (Forlenza et al, 2009). At the same time, inos gene expression is up-regulated in head kidney, spleen, PBL and liver leading to NO production and a dramatic increase in serum nitrite levels and tissue nitration (Forlenza et al, 2008b;Joerink et al, 2006;Saeij et al, 2000Saeij et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%